Characterization of external cross-talk from silicon photomultipliers in a liquid xenon detector - D. Gallacher; A. de St. Croix; S. Bron; B. M. Rebeiro; T. McElroy; S. Al Kharusi; T. Brunner; C. Chambers; B. Chana; Z. Charlesworth; E. Egan; M. Francesconi; et al. (European Physical Journal C: Particles and Fields)
Abstract The Light-only Liquid Xenon experiment (LoLX) employs a small-scale detector equipped with 96 Hamamatsu VUV4 silicon photomultipliers (SiPMs) submerged in 5 kg of liquid xenon (LXe) to perform characterization measurements of light production, transport and detection in xenon. In this work, we perform a novel measurement of the “external cross-talk” (ExCT) of SiPMs, where photons produced in the avalanche escape the device and produce correlated signals on other SiPMs. SiPMs are the photodetector technology of choice for next generation rare-event search experiments; understanding the sources and effects of correlated noise in SiPMs is critical for producing accurate estimates of detector performance and sensitivity projections. We measure the probability to observe ExCT through timing correlation of detected photons in low-light conditions within LoLX. Measurements of SiPM ExCT are detector dependent; thus the ExCT process is simulated and modelled using the Geant4 framework. Utilizing simulations, we determine the average transport and detection efficiency for ExCT photons within LoLX, a necessary input to extract the true ExCT probability and detector independent photon emission intensity. For an applied overvoltage of 4 V and 5 V, we measure a mean number of photons emitted into LXe per avalanche of $$0.5^{+0.3}_{-0.2}$$ 0 . 5 - 0.2 + 0.3 and $$0.6^{+0.3}_{-0.2},$$ 0 . 6 - 0.2 + 0.3 , respectively. Using an optical model to describe photon transmission through the SiPM surface, this corresponds to an estimated photon yield inside the bulk silicon of $$20^{+11}_{-9}$$ 20 - 9 + 11 and $$25^{+12}_{-9}$$ 25 - 9 + 12 photons per avalanche. The relative increase in intensity of SiPM ExCT emission between 4 and 5 V is consistent with expectation for the linear increase of gain with respect to overvoltage.